2021
DOI: 10.1111/are.15513
|View full text |Cite
|
Sign up to set email alerts
|

Sperm cryopreservation of Prochilodus lineatus throughout the same reproductive season

Abstract: The aim of this study was to determine the effect of seasonality on post‐thaw sperm quality in Prochilodus lineatus. Sperm from 43 males was cryopreserved throughout the reproductive season (November–March). Fresh sperm quality, concentration, volume, seminal plasma pH, osmolality and ion concentration were analysed. Post‐thaw sperm was analysed for its motility rate, velocities, beat‐cross frequency, cell morphology, oxidative stress and fertilization capacity. Prochilodus lineatus fresh sperm yielded high‐qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
(115 reference statements)
0
4
0
2
Order By: Relevance
“…These variations in sperm concentration in individuals within the same genus or species are linked to the season (8,9) , nutritional status (3,34) , water quality (35) , animal weight (14) , and the type and dose of the hormone used (10,27) . For instance, in an experiment evaluating the reproductive performance of Brycon orbygnianus and Prochilodus lineatus treated with buserine extract, Paulino et al (10) found that this hormone inducer provided a more homogenous response in sperm concentration of P. lineatus compared with B. orbygnianus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These variations in sperm concentration in individuals within the same genus or species are linked to the season (8,9) , nutritional status (3,34) , water quality (35) , animal weight (14) , and the type and dose of the hormone used (10,27) . For instance, in an experiment evaluating the reproductive performance of Brycon orbygnianus and Prochilodus lineatus treated with buserine extract, Paulino et al (10) found that this hormone inducer provided a more homogenous response in sperm concentration of P. lineatus compared with B. orbygnianus.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm concentration can be used to assess the volume of fresh or post-thawed sperm that will be directed to artificial fertilization procedures, helping to determine the most suitable insemination dose (6,7) . It can be also employed to identify the range of sperm production during the breeding season (8,9) , the response to hormonal treatment (10) , and differences between bred and wild males (4) . Sperm concentration may be estimated by (a) sperm count using a hemocytometer, (b) spermatocrit reading, (c) flow cytometry, and (d) optical density by spectrophotometry.…”
Section: Introductionmentioning
confidence: 99%
“…Streit Jr. et al (2008) found high rates of sperm pathology in gilthead sea bream (Salminus maxillosus) semen quality parameters in captivity. Egger et al (2021) evaluating seminal parameters of Prochilodus lineatus between the November and March, observed higher sperm concentration in November, better motility rate in November, January and February, and longer duration of motility time in January.…”
Section: Introductionmentioning
confidence: 99%
“…Anim. Bras., V24, e-74695P durante a estação reprodutiva (8,9) , a resposta ao tratamento hormonal (10) e as diferenças entre machos criados e selvagens (4) . A concentração espermática pode ser estimada por (a) contagem de espermatozoides usando um hemocitômetro, (b) leitura de espermatócrito, (c) citometria de fluxo e (d) densidade óptica por espectrofotometria.…”
Section: Introductionunclassified